Comparison of Three Digestion Methods for Heavy Metals Determination in Soils and Sediments Materials by ICP-MS Technique - Geana, E.I.; Iordache, A.M.; Voica, C.; Culea, M.; Ionete, R.E. (Asian Journal of Chemistry, 2011)
The measurement of elements concentration in soil and sediment is generally a combination of a digestion procedure for dissolution of elements and a subsequent measurement of the dissolved elements. It is important to evaluate different digestion methods to accurately determine the metals concentration. Therefore, three digestion procedures have been tested on soil standard reference material and Romanian soils and sediments samples for determination of heavy metals by inductively coupled plasma mass spectrometry (ICP-MS). The first is an open-vessel digestion with concentrated acids: HNO3 + HF and the others two are microwave-assisted concentrated acids digestion A: HNO3 + HF, B: HNO3 + HF + HCl. Owing to the multi-elemental capabilities of the ICP-MS technique, in these materials eight elements were determined, at mg/kg concentrations. In general, the microwave acid digestion with HNO3 + HF + HCl was overall the best procedure for determining concentration of most metals in SRM and Romanian soils and sediments.